Determinants Of Waqf Interest In Jakarta Al-Azhar Waqf Institution - MH. Ainulyaqin; Adrianna S.R; Done A.M.P (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
This study aims to determine the influence of social stratification and religiosity on the interests of waqf donation in waqf institutions. Determination of samples using purposive sampling method so that the number of samples obtained 100 waqif Wakaf Al Azhar in 2021. The analysis techniques used are ttest, Ftest, determination coefficient (R2), and multiple regression test. Data processing in this study using IBM SPSS Statistics 25. The results of the Ttest showed that income variables did not have a positive and significant influence on the interest of waqf donation, work variables did not have a positive and significant influence on the interest of waqf donation, educational variables did not have a positive and significant influence on the interest of waqf donation, and religious variables had a positive and significant influence on the interest of waqf donation. Ftest's test results show that income, employment, education, and religiosity together affect the interest in donating waqf. While the result of the coefficient of determination (R2) of 0.427 means that the contribution of independent variables (income, employment, education, and religiosity) affects the variable dependent (waqf interest) by 42.7% while the remaining 57.3% is influenced by other variables outside the research model.